2018
DOI: 10.1016/j.jmb.2018.03.020
|View full text |Cite
|
Sign up to set email alerts
|

RelA-Containing NFκB Dimers Have Strikingly Different DNA-Binding Cavities in the Absence of DNA

Abstract: The main nuclear factor kappa B transcription factor family members RelA-p50 heterodimer and RelA homodimer have different biological functions and show different transcriptional activation profiles. To investigate whether the two family members adopt a similar conformation in their free states, we performed hydrogen-deuterium exchange mass spectrometry, all-atom molecular dynamics simulations, and stopped-flow binding kinetics experiments. Surprisingly, the N-terminal DNA-binding domains adopt an open conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Deuterium uptake for each peptide was calculated by comparing the centroids of the mass envelopes of the deuterated samples with the undeuterated controls. Back-exchange correction factors were applied as previously reported 44 The Y-axis limit for each plot reflects the total number of amides within the peptide that can possible exchange. Each plot includes the peptide MH+ value, sequence, and sequential residue numbering.…”
Section: Methodsmentioning
confidence: 99%
“…Deuterium uptake for each peptide was calculated by comparing the centroids of the mass envelopes of the deuterated samples with the undeuterated controls. Back-exchange correction factors were applied as previously reported 44 The Y-axis limit for each plot reflects the total number of amides within the peptide that can possible exchange. Each plot includes the peptide MH+ value, sequence, and sequential residue numbering.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting peptides were captured at 0 °C on a BEH C18 Vanguard pre-column, separated by analytical chromatography (Acquity UPLC BEH C18, 1.0 × 50 mm, Waters Corporation) using a 7–85% gradient acetonitrile in 0.1% formic acid over 7.5 min, and electrosprayed into the Waters SYNAPT G2Si quadrupole time-of-flight mass spectrometer. The mass spectrometer settings and peptide identification methods have been reported previously 44 . The experiments were performed in triplicate, and independent replicates of the triplicate experiment were performed to verify the results.…”
Section: Methodsmentioning
confidence: 99%
“…Conformational Heterogeneity in Free NFĸB. Previous coarse-grained (14) and all-atom MD simulations (5) showed that the two NTDs in a NFĸB dimer can rotate and translate with respect to each other. To experimentally probe the conformational heterogeneity of the NTDs, we carried out TIRF-based smFRET experiments by labeling each NTD with either a donor or acceptor fluorophore.…”
Section: Resultsmentioning
confidence: 99%